THE HYPERFINE STRUCTURES OF CUCL AND CUBR IN THEIR GROUND-STATES STUDIED BY MICROWAVE FOURIER-TRANSFORM SPECTROSCOPY - Low, R; Varberg, T; Connelly, J; Auty, A; Howard, B; Brown, J (1993)
The hyperfine structure of the J = 1 ← 0 rotational transition of CuCl as well as the J = 3 ← 2, 2 ← 1, and 1 ← 0 rotational transitions of CuBr in the v = 0 vibrational level have been investigated using a microwave Fourier transform spectrometer. The molecules were produced by laser ablation of the copper halide followed by an axial supersonic expansion into a near-semiconfocal Fabry-Perot cavity. The analysis of the hyperfine structure yielded improved values of the rotational and electric quadrupole constants and determined the nuclear spin-rotation constants for the first time. The physical implications of these results are discussed. © 1993 Academic Press. All rights reserved.